Effects of subjective perceptions of indoor visual environment on visual-related physical health of older people in residential care homes. (1st June 2023) - Wang, Chendi; Leung, Mei-yung
Abstract: Aging profoundly affects people's visual functions, and older persons generally show a declination of visual abilities. The indoor visual environment (IVE) in residential care homes (RCHs) is vital to ensure the visual-related physical health of older people (i.e., general vision, functional vision, visual acuity, physical discomfort, and injuries). The IVE, including opening design, interior design, and lighting conditions components, should be designed to satisfy older people's special visual needs. Hence, this study aims to investigate the effects of older people's subjective perceptions of the IVE on their visual-related physical health. In total, 197 questionnaires were collected from older persons living in RCHs. The integrated IVE–Visual-related Physical Health model was established based on multiple statistical methods for older residents in RCHs. The model revealed that the view out, window, corridors, furniture locations, curtains or louvers, handrails, and light level significantly affected the visual-related physical health of older people. Practical recommendations were proposed, including beds and seats near the windows with beautiful scenery, corridors with night lights and unblocked vision, automatic curtains with light sensors, handrails with a high color contrast with the background walls, minimum 200lx ambient lighting, etc. This study's findings provide valuable insight into enhancing the IVE in RCHs for older people's visual-related physical health. Highlights: Visual-related physical health and indoor visual environment (IVE) factors are identified. Three opening design factors predict their visual-related physical health. Three interior design factors positively affect their visual-related physical health. One lighting condition factor positively influences their visual-related physical health. An IVE–Visual-related Physical Health model for older people is established.